Appendix 1: Morphological Tables - Nesset, Tore (Septentrio Educational, 2015)
This appendix contains morphological tables from chapters 4–8 as a reference tool. If you need to identify a form in an Old Rusian text, it may be quicker and more efficient to look for it in this appendix than to locate the relevant paradigm in chapters 4–8.